Characteristics of anesthetic and surgical tactics in treatment of a patient with a giant thyroid mass in a cancer center (clinical case) - D. A. Rozenko; M. A. Engibaryan; D. A. Kharagezov; M. V. Zhenilo; N. N. Popova; M. V. Bauzhadze; E. A. Marykov (Южно-Российский онкологический журнал, 2024)
This paper describes an example of radical surgical treatment of a patient with a giant retrosternal goiter complicated by compression of the organs of the neck and mediastinum. Considering all the risks and possible complications, we should take into account the fact that enlarged thyroid (T) body with retrosternal location can cause displacement and stenosis of the trachea and esophagus, and dislocation of large vessels and nerves of the mediastinum. This anatomical specificity is an imminent threat to successful treatment, and it also carries a certain risk of asphyxia and sudden death of the patient. In this clinical case, radical surgical treatment in this patient included sequential mobilization in two pleural cavities, and then the total removal of T through the traditional surgical access. The anesthetic complexity to support the surgical intervention involved both difficult intubation due to tracheal stenosis, and also the required separate ventilation of the lungs to visualize anatomical structures and mobilize a multinodular formation in two pleural cavities. Standard methods of artificial lung ventilation could be ineffective and even dangerous in this case due to the location and size of the tumor. We focused our attention on high-frequency ventilation (HFV), the best method of respiratory support during surgeries for tracheal and bronchial pathologies. The main task of the anesthetic team in this clinical case was to prevent the development of hypercapnia and hypoxia during intubation of the stenotic tracheal segment, and then adequate ventilation of the lungs with reduced area of proper gas exchange due to bilateral surgical pneumothorax. Thus, the full treatment was carried out due to the only safe method of compensating lung ventilation with anesthesia by HFV. The applied HFV method creates an adequate gas exchange in the lungs due to the small ventilation volume and high frequency of respiratory cycles per minute. HFV both prevented the development of threatening complications during intubation of the stenotic tracheal area and ensured an adequate gas exchange during successive thoracoscopic stages of thyroid tumor mobilization.